PRINCIPAL’S LEADERSHIP OF MORAL AND VALUE-BASED INDONESIA’S 2030 VISION - Anis Fauzi; Nana Suryapermana (JURNAL TARBIYAH, 2020)
This study purpose of describing the importance of the principal's ability to understand the values develop in the life of the community around the school and be aware of the dynamics of moral development of society in general in order to achieve Indonesia's 2030 vision. This study uses a literature study method and through observation of the lives of people around schools at Banten Province, Indonesia. Findings this study is the majority of principals did not understand optimally about the values of life that grow and develop in the community around the school they managed and did not realize the dynamics of the development of moral society in general. Research Implications is all principals in Indonesia should be more severe in understanding the values of life that develop in the community around the school and be more aware of the dynamics of community moral development in general, which has an impact on the sustainability of education programs in schools that he led. Practical Implications is If the principal does not do these two things (Leadership of Moral and  Value), then Indonesia's 2030 Vision that we aspire to is challenging to